Effect of Fetal Calf Serum and Mid Estrus Cow Serum on In Vitro Maturation and Fertilization of Oocytes from Crossbred Cattle in the Tropics - Vettical, Binoy S (International Journal of Applied Sciences and Biotechnology, 2016)
The objective of the study was to examine the effect of fetal calf serum (FCS) and mid estrus cow serum (ECS) in culture media on in vitro maturation (IVM) and in vitro fertilization (IVF) of oocytes from crossbred cattle in the tropics. Oocytes from abattoir ovaries were cultured in three different maturation media at 39oC temperature, 5% CO2 tension with maximum humidity for 24 h. TCM-199 containing 25mM HEPES, 1mM glutamine L, 2.2mg/mL sodium bicarbonate, antibiotics, 22 µg/mL pyruvate, 1µg/mL estradiol-17β, 0.5µg/mL FSH and 0.06 IU hCG without serum supplement used as treatment-1 and the above media were further supplemented with 10% FCS as treatment-2. In treatment-3, instead of 10% FCS, 20% heat inactivated ECS (serum collected in mid estrum) was used as serum supplement. Oocytes with maximum degree of cumulus expansion were selected as matured and used for further IVF studies using frozen semen. The IVF medium consisted of Fert-TALP medium supplemented with 1µM epinephrine, 10µM hypotaurine, 20µM pencillamine and 0.56µg/ml heparin. Culture conditions set for IVF were 39oC temperature, 5% CO2 tension with maximum humidity. Oocytes showing sperm penetration evidence like presence of enlarged sperm head, male pronuclei with its accompanying sperm tail in the cytoplasm, oocytes with two pronuclei and a clear second polar body but without a sperm tail were considered as fertilized. Significantly higher result of cumulus expansion percentage (p< 0.05) was observed when oocytes matured in media supplemented with FCS as compared to other two treatments. There was no influence of source of serum in maturation media on further IVF of matured oocytes in this study. Int J Appl Sci Biotechnol, Vol 4(3): 308-310